Efektifitas Pengembangan E-Learning dengan LMS Moodle dan Laboratorium Virtual Pada Pendidikan Tinggi - Faiza Rini; Tanto; Fery Purnama (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2021)
This study aims to analyze how effective the development of e-learning and virtual laboratories in the universities. Because so far students have difficult in finding lecture references and besides that the learning process cannot be monitored by the institution and the unavailability of media used to support practicum courses in the laboratory. The method used in this research is research and development with five steps including: a. Conduct product analysis to be developed b. Develop initial product c. Revision d. Small-scale field trials and product revisions e. Large-scale field trials and final products. To measure the effectiveness of e-learning used the Technology Acceptanced Model (TAM) using 2 factors including a. usefullnes factors (users believe that their performance will improve by using this system) and b. ease of use (the user believes that the use of this system will free from the trouble). To analyze how effective the use of e-learning and virtual laboratories is, the researchers used a sample with 20 lecturers as respondents. From the results of the research conducted, it can be concluded that 92% of lecturer respondents agree and are effective towards the developed e-learning and virtual laboratory